Decoupled Land and Ocean Temperature Trends in the Early‐Middle Pleistocene. Issue 17 (7th September 2022) - Lu, Hongxuan; Liu, Weiguo; Yang, Hong; Leng, Qin; Liu, Zhonghui; Cao, Yunning; Hu, Jing; Sheng, Weijuan; Wang, Huanye; Wang, Zheng; Zhang, Zeke; Sun, Youbin; et al.
Abstract: Record of long‐term land temperature changes remains ephemeral, discontinuous, and isolated, thus leaving the common view that Pleistocene land temperature evolution should have followed ocean temperatures unconfirmed. Here, we present a continuous land surface temperature reconstruction in the Asian monsoon region over the past 3.0 Myr based on the distribution of soil bacterial lipids from the Chinese Loess Plateau. The land temperature record indicates an unexpected warming trend over the Pleistocene, which is opposite to the cooling trend in Pleistocene ocean temperatures, resulting in increased land‐sea thermal contrast. We propose that the previously unrecognized increase of land‐sea thermal contrast during much of the Pleistocene is a regional climate phenomenon that provides a likely mechanism in favor of the long‐term enhancement of the Pleistocene East Asian summer monsoon. Plain Language Summary: Numerous sea surface temperature (SST) records indicate long‐term gradual cooling over the Pleistocene, whereas the East Asian summer monsoon (EASM) appears to have strengthened during this period. Land‐sea thermal contrast is thought to have an important influence on the intensity of the EASM, but the lack of land surface temperature (LST) records from monsoonal regions prevents the assessment of its role in driving monsoonal changes. Here, we present a 3‐Myr‐long LST record from the Chinese Loess Plateau, displaying a unique long‐term warming trend over the Pleistocene, different from the trajectories of SST records. We propose that the decoupling of long‐term land and sea temperatures, and thus the increase of land‐sea thermal contrast, provides a simple interpretation for the otherwise paradox, strengthening of the EASM over the Pleistocene. This study presents much needed original LST data that support novel interpretations on a mechanism for important paleoclimate phenomenon in East Asia with implications to the entire terrestrial ecosystem during the critical period of earth history. Key Points: Three million years of continuous land surface temperatures reconstructed based on soil bacterial lipids The land temperature record indicates an unexpected warming trend over the Pleistocene Increasing land‐sea thermal contrast facilitated the long‐term intensification of Pleistocene East Asian summer monsoon